The Role of ‘Modul Pembinaan Karakter (MPK)’ in Building a Superior Personality in Trainees: a Case Study - Darus, Darwina; Ibrahim, Abu Bakar; Dawi, Amir Hassan; Selamat, Abu Zarrin (Jurnal Ilmiah Peuradeun, 2022)
Program Latihan Khidmat Negara (PLKN) is a national agenda that aims to train Malaysian youths to become a generation of more excellent heirs and the core of development and the backbone of the country's future. MPK is a module implemented to build prominent personality in trainees as an excellent and quality human development process. The implementation of MPK in the PLKN camp is focused on personality elements that form discipline and self-awareness of essential matters and exemplary personal qualities with noble values that are the core of community life. Thus, this study analyzed the role of MPK in building a distinguished personality in trainees: a study at the Tawau PLKN Camp, Sabah. The variables involved in this study were character building, prominent personality, trainee, and camp. All variables were examined for their manifestation through unity, character, leadership, confidence, self-strength, and national integration. The design of this study was conducted by combining quantitative and qualitative approaches, namely questionnaires and interview sessions. This study was conducted in Tawau for group 2 Series 9/2014. A total of 142 trainees were directly involved in the questionnaire study, and 90 respondents were involved in the interview session. The method used to analyze the collected data was to find the average score given by the respondents. Generally, the average score for all items studied ranged from 4.07 (agree) on a scale of 1-5. Overall, the findings from this study can be re-evaluated so that MPK can be reabsorbed in PLKN in the future to build healthy young people in terms of positive identity and physical and spiritual to form a national leadership that can compete in the eyes the world of the future.